El Salvador a fin del siglo - Guido Béjar, Rafael; Roggenbuck, Stefan (San Salvador, El Salvador : Fundación Konrad Adenauer, 1995)
"Eight essays focusing primarily on political economy and demography. Most interesting are Molina on the ’exhaustion’ of yet another externally ’imposed’ economic model (i.e., neoliberalism), with a call for a truly integrated, national model of development; Montoya’s solid description of agriculture; and the longest piece, Huezo’s manifesto on cultural decadence and renovation"--Handbook of Latin American Studies, v. 57.
América Latina : un subcontinente en transición / Stefan Roggenbuck -- El Salvador : ¿una democracia diferente? / Rafael Guido Béjar -- Un siglo de modelos económicos impuestos y la necesidad de concerta al final del siglo XX / Hugo Molina -- La realidad agraria en El Salvador de fines de siglo / Aquiles Montoya -- Reordenamiento demográfico y exportación de población. El Salvador a finales del siglo XX / Oscar Armando Morales Velado -- La reconversión laboral hacia la informalidad y las estrategias laborales en El Salvador / Rafael Guido Béjar -- La casa en llamas : decadencia y renovación cultural en El Salvador / Miguel Huezo Mixco -- Crecimiento urbano, cuencas hidrográficas y destrucción medioambiental : el caso del Área Metropolitana de San Salvador / Ricardo Francisco Vasquez G.
Incluye referencias bibliográficas.
general
Keywords: Agricultura -- El Salvador -- Aspectos económicos; América Latina -- Aspectos políticos -- Siglo XX; América Latina -- Condiciones económicas -- Siglo XX; El Salvador -- Concidiciones económicas -- 1945-; El Salvador -- Condiciones sociales; El Salvador -- Política y gobierno -- 1992-